THE EFFECT OF GIVING AND EMPTY PALM OIL BUNCHES COMPOST AND FERTILIZER AT UTISOL LAND TOWARD GROWTH SWEET CORN (Zea mays saccharata L.) - Adriani '; Nelvia '; Rosmimi ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The Research aims to study the effect of application of composting of oil palm empty fruit bunch ( compost of OPEFB) and fertilizer of N, P and K to the growth and yield of sweet corn in Ultisol. The research conducted at Kampar District, Riau Province from September to December 2011. This reseach used completely randomized design (CRD) consisting of 10 treatment; 0, 20, 40 and 60gram OPEFB compost/polybag (A,B,C and D); 20, 40, and 60gram/polybag OPEFB compost/polybag +fertilizer of N,P, K with half the recommended dose (E,F and G); 20, 40, and 60gram OPEFB compost + fertilizer of N,P and K with recommended dosage ( H,I and J) each treatment was repeatet 3 time. The parameters measured were height plant, diameter of cobs, long of cobs , weight cobs, weight of cron cobs without cron husk. The results showed that the application of 60 gram/polybag with OPEFB compost/polybag +fertilizer, N, P and K recommended dosage can the growth and yield of sweet corn highest compered with the control and othe treatments. Keyword: Empty Palm Bunch, NPK fertilizer, Ultisol, Sweet corn